2022
DOI: 10.1073/pnas.2123065119
|View full text |Cite
|
Sign up to set email alerts
|

The global succinylation of SARS-CoV-2–infected host cells reveals drug targets

Abstract: SARS-CoV-2, the causative agent of the COVID-19 pandemic, undergoes continuous evolution, highlighting an urgent need for development of novel antiviral therapies. Here we show a quantitative mass spectrometry-based succinylproteomics analysis of SARS-CoV-2 infection in Caco-2 cells, revealing dramatic reshape of succinylation on host and viral proteins. SARS-CoV-2 infection promotes succinylation of several key enzymes in the TCA, leading to inhibition of cellular metabolic pathways. We demonstrated that host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Additionally, succinylation is known to provide a link between metabolism and protein function in the nervous system and in neurological diseases, rendering deeper understanding of its mechanism highly interesting 4 . Likewise, succinylation has also been shown to be substantially upregulated in the early phases of infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), suggesting that succinylation inhibitors may be able to reduce viral replication to treat COVID-19 5 . Interestingly, succinylation is observed in diverse organisms, including bacteria, yeast, and mouse and these sites are also frequent targets of acetylation (another important PTM) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, succinylation is known to provide a link between metabolism and protein function in the nervous system and in neurological diseases, rendering deeper understanding of its mechanism highly interesting 4 . Likewise, succinylation has also been shown to be substantially upregulated in the early phases of infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), suggesting that succinylation inhibitors may be able to reduce viral replication to treat COVID-19 5 . Interestingly, succinylation is observed in diverse organisms, including bacteria, yeast, and mouse and these sites are also frequent targets of acetylation (another important PTM) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Co-immunoprecipitation was performed as previously described ( Liu et al, 2022 ). In brief, cells were lysed in the lysis buffer containing protease and phosphatase inhibitor cocktail (Selleck, Houston, Texas, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical and cellular studies demonstrated that SIRT5 plays a significant role in the SARS-CoV-2 infection, even though two different studies point towards opposite conclusions. Indeed, while both reports agree that SIRT5 interacts with SARS-CoV-2 non-structural viral protein 14 (NSP14), they have opposite conclusions by suggesting that SIRT5 could act either as a proviral factor [ 145 ] or it could inhibit viral replication [ 146 ].…”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%
“…A completely different perspective has emerged from a recent study by Liu and colleagues, who claim that SIRT5 inhibits viral growth due to desuccinylase activity that results from its interaction with NSP14 [ 146 ]. Experiments executed in CRC Caco-2 cells indicate that protein succinylation is particularly upregulated during the early stages of infection and is positively correlated with the period of viral infection [ 146 ], overall suggesting that this may be a host response during SARS-CoV-2 infection. The membrane glycoprotein (M) and nucleocapsid (N) proteins are succinylated ~24 h post-infection, demonstrating that succinylation occurs after translation during viral replication (between 12- and 24-h post-infection).…”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%